Analisis Faktor-faktor yang Berhubungan dengan Kejadian Hiperemesis Gravidarum Di Rumah Sakit Bhayangkara Palembang Tahun 2020 - Yulia Anggraini; Siti Aisyah; Sendy Pratiwi Rahmadhani (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Nausea and vomiting in pregnancy is a physiological thing, the influence of hormones in pregnancy Human Chorionic Gonadotropin (HCG) causes nausea and vomiting. The purpose of this study is to know the relationship between education, age and parity simultaneously with Hyperemesis Gravidarum at Bhayangkara Hospital Palembang in 2020. This research is a quantitative research type of descriptive analytic research with a cross sectional approach. The population in this study were all pregnant women who were recorded in the medical records of Bhayangkara Hospital in 2020 amounted to 162 respondents. The sample size is determined by the slovin formula and obtained by 62 respondents. Samples were taken using simple random sampling technique. The results of the univariate analysis were 43 (69.4%) respondents who experienced hyperemesis gravidarum and 19 (30.6%) who did not experience hyperemesis gravidarum, 33 (53.2%) low educated respondents and 33.2% high educated respondents. 29 (46.8%), age respondents who are at risk are 36 (58.1%) and those who are not at risk are 26 (41.9%). mothers with low parity amounted to 40 (64.5%) and mothers with high parity amounted to 22 (35.5%). The results of the bivariate analysis showed that there was a significant relationship between education with a p value of 0.000, age with a p value of 0.049 and parity with a p value of 0.001 simultaneously with hyperemesis gravidarum at Bhayangkara Hospital Palembang in 2020. The suggestions for health workers from this study It is hoped that health workers at Bhayangkara Hospital Palembang, can be alert to provide information and education to pregnant women regarding their pregnancy.